A New Explanation of Inflammation in Rheumatoid Arthritis Patients With Respect to Claudin-5, Matrix Metalloproteinase-9, and Neuroserpin - Sevil Arabacı TAMER; Gönül GÜROL; İbrahim TEKEOĞLU and Halil HARMAN and İhsan Hakkı ÇİFTÇİ (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate the relationship between neuroserpin (NSP) and claudin-5, as well as matrix metalloproteinase-9 (MMP-9), with respect to clinical activity of disease in patients with rheumatoid arthritis. Patients and methods: The study included a total of 75 patients (18 males, 57 females; mean age 48.12±11.23 years; range 20 to 60 years) who were admitted to the rheumatology outpatient facility at the Medical Faculty Hospital, Sakarya University, in October 2014. Patients were divided into four groups based on their Disease Activity Score 28 (DAS28) scores as remission group (n=16, DAS28 <2.6), low disease activity group (n=16, DAS28 between 2.6-3.2), moderate disease activity group (n=28, DAS28 between 3.2-5.1), and high disease activity group (n=15, DAS28 >5.1). Ten healthy subjects (HS) served as controls. Results: Claudin-5, MMP-9, and NSP levels were significantly different in rheumatoid arthritis patients compared to HS (p=0.035, 0.026, and 0.014, respectively). Additionally, there were no differences between claudin-5 levels and disease activity among all RA groups. However, compared to HS, patient groups showed a significant difference (p=0.035) in terms of claudin-5 levels. Serum levels of MMP-9 were significantly different in moderate disease activity group compared to HS (p=0.013). Levels of NSP were significantly different in moderate disease activity and high disease activity groups compared to HS (p=0.008 and 0.031, respectively). Conclusion: Our study demonstrated the differential associations of endothelial function/dysfunction biomarkers and disease activity in rheumatoid arthritis. How and why this impairment occurs is not fully understood and more data regarding NSP, MMP, and claudin expression in plasma are warranted.